Roads Disrupt Frugivory and Seed Removal in Tropical Animal-Dispersed Plants in French Guiana - Coutant, Opale; Boissier, Olivier; Ducrettet, Manon; Albert-Daviaud, Aurélie; Bouiges, Axelle; Dracxler, Caroline Marques; Feer, François; Mendoza, Irene; Guilbert, Eric; Forget, Pierre-Michel (Frontiers in Ecology and Evolution, 2022)
Ecological interactions are being affected at unprecedented rates by human activities in tropical forests. Yet, the continuity of ecological functions provided by animals, such as seed dispersal, is crucial for forest regeneration and species resilience to anthropogenic pressures. The construction of new roads in tropical forests is one of the main boosters of habitat destruction as it facilitates human access to previously isolated areas and increases defaunation and loss of ecological functions. It, therefore, becomes increasingly urgent to rapidly assess how recently opened roads and associated anthropogenic activities affect ecological processes in natural habitats, so that appropriate management measures to conserve diversity can be taken. In this study, we aimed to evaluate the effects of anthropogenic pressures on the health status of a mature rainforest crossed by a newly opened road in French Guiana. For this, we combined different methods to conduct a rapid assessment of the forest’s health status. Firstly, we evaluated the activity of frugivores using camera traps deployed in four forest patches located near (<1 km) ecological corridors preserved as canopy bridges over the road during the fruiting periods of four animal-dispersed tree species. Secondly, we analyzed the fate of seeds enclosed in animal-dispersed tropical fruits by calculating the proportions of fruits consumed and seeds removed (either dispersed or predated) by frugivores. Results show that the proportion of fruits opened and consumed was lower in the forest areas located near the road than in the control forest, and this difference was more significant for plant species strictly dependent on large-bodied primates for seed dispersal than for species relying on both primates and birds. Camera traps showed the presence of small primates and kinkajous feeding on Virola fruits in the forest impacted by the road, where large primates were absent. It is thus likely that smaller frugivores exert a compensatory effect that maintains ecological functions near the road. Despite efforts made to preserve forest continuity through ecological corridors, anthropogenic pressures associated with road proximity are affecting wildlife and disrupting associated ecological functions crucial for plant regeneration, contributing to further forest degradation.